Collagen molecular organization preservation in human fascia lata and periosteum after tissue engineering - Vettese, Julia; Manon, Julie; Chretien, Antoine; Evrard, Robin; Fievé, Lies; Schubert, Thomas; Lengelé, Benoît G.; Behets, Catherine; Cornu, Olivier (Frontiers in Bioengineering and Biotechnology, 2024)
Large bone defect regeneration remains a major challenge for orthopedic surgeons. Tissue engineering approaches are therefore emerging in order to overcome this limitation. However, these processes can alter some of essential native tissue properties such as intermolecular crosslinks of collagen triple helices, which are known for their essential role in tissue structure and function. We assessed the persistence of extracellular matrix (ECM) properties in human fascia lata (HFL) and periosteum (HP) after tissue engineering processes such as decellularization and sterilization. Harvested from cadaveric donors (N=3), samples from each HFL and HP were decellularized following five different chemical protocols with and without detergents (D1-D4 and D5, respectively). D1 to D4, consisted of different combinations of Triton, Sodium dodecyl sulfate and Deoxyribonuclease, while D5 is routinely used in the institutional tissue bank. Decellularized HFL tissues were further gamma-irradiated (minimum 25kGy) in order to study the impact of sterilization on the ECM. Polarized light microscopy (PLM) was used to estimate the thickness and density of collagen fibers. Tissue hydration and content of hydroxyproline, enzymatic crosslinks, and non-enzymatic crosslinks (pentosidine) were semiquantified with Raman spectroscopy. ELISA was also used to analyze the maintenance of the decorin (DCN), an important small leucine rich proteoglycan for fibrillogenesis. Among the decellularization protocols, detergent-free treatments tended to further disorganize HFL samples, as more thin fibers (+53.7%) and less thick ones (-32.6%) were recorded, as well as less collagen enzymatic crosslinks (-25.2%, p = 0.19) and a significant decrease of DCN (p = 0.036). GAG content was significantly reduced in both tissue types after all decellularization protocols. On the other hand, HP samples, were more sensitive to the D1 detergent-based treatments, with more disrupted collagen organization and greater, though not significant, loss of enzymatic crosslinks (-37.4%, p = 0.137). Irradiation of D5 HFL samples, led to a further and significant loss in the content of enzymatic crosslinks (-29.4%, p = 0.037) than what was observed with the decellularization process. Overall, the results suggest that the decellularization processes did not significantly alter the matrix. However, the addition of a gammairradiation is deleterious to the collagen structural integrity of the tissue.